Analysis on the evolution and innovation of online game industry using meta-frontier analysis. Issue 1 (2nd January 2017) - Lee, Daeho; Lee, Sangwon; Kim, Jang Hyun
Abstract : The game industry has made great progress in the recent decade, and recently other layers in the information and communication technology ecosystem affect the innovation and evolution of the game industry with the emergence of the Internet and online games. This paper estimates the changes in efficiency by data envelopment analysis and meta-frontier analysis in order to investigate how the online game industry evolves. As a result, there were enterprises that lifted up the production function of the game industry by innovation when the external factors such as diffusion of the broadband Internet network and mobile Internet environment affected the game industry. The result implies that the steady increment of meta-frontier efficiency means that the industry is growing by innovation or imitation, or both.